Pengembangan E-Module dan Tutorial Matakuliah Pengembangan Media Audio Radio Jurusan Teknologi Pendidikan - Zainul Abidin (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2016)
Learning audio / radio media development course at the UM FIP department is expected to be able to make / develop various forms and formats with appropriate and appropriate patterns and procedures. The concepts that must be mastered are related to forms, patterns, formats, positions, procedures and how to use audio learning media. If this concept is not mastered, it will affect the quality of the development results. This stage is a very important stage before mastering the production of audio / radio media, it is necessary to master the concepts (preproduction), including: 1) various forms, patterns, formats, positions, procedures and ways of using them, 2) various ways of making audio media learning. In general, development is related to (1) drafting, (2) script writing, (3) production, (4) evaluation. (Arif S. Sadiman, 2007: 97-174). From the description above, it can be explained the phases of the model / approach used in product development, including 1). Identification of needs, 2). Problem Formulation, 3). Formulation of Success Measurement Tools, 4). Production Process, 5). Evaluation, 6). Implementation. The impact of this media development is an increase in the knowledge, attitudes, and development abilities of students. The results of the validation of the learning design experts were 92% and the Media Experts were 90%, this illustrates that the development of learning media really meets the provisions and principles of learning.